Bersama Javidan Khirad Seyyed Hossein Nasr - Ainur Rofiq Al-Amin (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2007)
On the issue of religious pluralism one may find different currents of thoughtranging from that which rejects it to that which accepts it. A part from this, the issue ofreligious pluralism has also provoked scholars of different backgrounds ?Muslim andWestern scholars- to have their say concerning this very important problem. One ofthose scholars is Seyyed Hossein Nasr who proposed what he calls Javidan Khirad. Thispaper is destined to explore this concept and the implication that emerges there of.